Rancang Bangun Sistem Adaptive Cruise Control (ACC) dengan Metode Fuzzy Logic pada Prototype Robo Car - Istiqomah, Aulia; Mohammad , Luthfansyah; Kurniawan, Muhammad Irham Agil (Jurnal Otomasi Kontrol dan Instrumentasi, 2025)
The rapid growth of four-wheeled vehicles in Indonesia has contributed to an increase in traffic accidents, where human error is a significant factor. Adaptive Cruise Control (ACC) is a technology that has been widely implemented in Advanced Driver Assistance Systems (ADAS) to improve driving safety. This study develops a Fuzzy Logic Controller (FLC)-based ACC system using ESP8266 as the main microcontroller to optimize adaptive vehicle speed control based on the distance to the object in front. This system is designed to process distance and speed data in real-time, allowing it to adjust the vehicle's speed without sudden changes. A fuzzy logic model was developed and validated through MATLAB simulations before being implemented into hardware. Test results indicate that the FLC-based ACC system can maintain a safe distance and dynamically regulate speed, exhibiting smoother speed transitions compared to conventional methods. A comparison between MATLAB simulation results and real-world implementations shows that the system can operate with high accuracy, despite differences due to environmental factors. With this success, this research proves that FLC can be a more flexible alternative in ACC systems and has the potential to be applied in the development of electric and autonomous vehicles in the future.